2017
DOI: 10.1161/jaha.116.004593
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Relationship Between Dairy Intake and Blood Pressure in Black and White Children and Adolescents Enrolled in a Weight Management Program?

Abstract: BackgroundThe DASH (Dietary Approaches to Stop Hypertension) clinical trials and other studies have demonstrated a relationship between diet and cardiovascular outcomes in adults, yet little is known of this relationship in children. Childhood obesity has reached epidemic proportions in the United States, with similar increases in hypertension among this population. The purpose of our study was to examine the association between dairy intake and blood pressure (BP) in a cohort of children and adolescents (aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Yuan et al indicated that high intake of dairy (≥ 2 servings per day) has antihypertensive effects on BP among children aged 8 to 10 years [ 42 ]. In a study by DellaValle et al [ 43 ], greater intakes of dairy products were associated with lower SBP in white but not black children and teens, suggesting the possible role of demographic factors including race in beneficial role of dairy products. Given that, the type of dairy products in terms of low- or high-fat, as well as different types of dairy products such as milk, yogurt, cheese was not identified in our study; this may justify the discrepancy in the results, because studies show that specific types of dairy products such as low-fat milk and milk products have inverse association with hypertension and there were no association with high-fat dairy or cheese [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al indicated that high intake of dairy (≥ 2 servings per day) has antihypertensive effects on BP among children aged 8 to 10 years [ 42 ]. In a study by DellaValle et al [ 43 ], greater intakes of dairy products were associated with lower SBP in white but not black children and teens, suggesting the possible role of demographic factors including race in beneficial role of dairy products. Given that, the type of dairy products in terms of low- or high-fat, as well as different types of dairy products such as milk, yogurt, cheese was not identified in our study; this may justify the discrepancy in the results, because studies show that specific types of dairy products such as low-fat milk and milk products have inverse association with hypertension and there were no association with high-fat dairy or cheese [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple binary logistic regression analyses (adjusted for age and BMI) and by categorising sleep duration into four groups (≤8 h, 8.1-8.9 h, 9.0-9.9 h, ≥10 h), shorter sleep duration was also shown to be a risk factor for increased BP. There are several studies examining the relationship between increased BP and various environmental conditions, other than sleep duration ( 22 , 23 , 24 , 25 , 26 ). In this present study, the only other significant environmental risk factor identified was location of the school the children or adolescents were attending and this was only true of the girls.…”
Section: Discussionmentioning
confidence: 99%
“…No signi cant correlation was found between BP and dairy products in the current study. Greater intakes of dairy products were associated with lower SBP in white but not black children and teens in Dellavalle et al study, suggesting that greater dairy products intake alone might be not bene cial for all races [30]. There was no signi cant relationship between meals and hypertension.…”
Section: Discussionmentioning
confidence: 81%